RISE: Humanitarian crises: the role of Islamic finance / Assoc. Prof. Dr Amirul Afif Muhamat - Muhamat, Amirul Afif (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Muslims have been practising Islamic finance since the time of Prophet Muhammad (peace be upon him). There are disparities, in terms of products, modes of transaction, and the manner the processes are governed. Nonetheless, the raison d'être of Islamic finance is to ensure that business transactions are conducted fairly for all parties involved; and the subject matter of the transactions are halal with benefits brought to mankind. This ethos is significant because Muslims consider their actions to be part of their submissions to Allah, which will be judged in the afterlife.